The Uneven Effect of COVID School Closures: Parents in Teleworkable vs. Non-teleworkable Occupations - Ainoa Aparicio Fenoll (Institute of Labor Economics (IZA), 2022)
Teleworking parents can better monitor and help their children with online learning. In this paper, I test whether parents' teleworkability affected children's online learning during Covid school closures. I use panel data from Invalsi, which includes the results of standardized tests given to all Italian students in grades 2 and 5 and parental characteristics. I compare changes in children's performance from grade 2 to grade 5 along two dimensions: whether they experienced Covid school closures between grade 2 and grade 5 and whether their parents work in teleworkable occupations. I also exploit variations in the length of Covid school closures and the use of online learning resources across Italian regions. My results show that one hundred school closure days widens the gap between children of teleworkable and nonteleworkable parents by 0.04 in language tests and 0.01 in maths tests.
Keywords: I24; J81; 330; teleworkability; online learning; COVID-19; parents